ANALISIS KEPUTUSAN KEPALA DESA DALAM PENGALOKASIAN DANA DESA UNTUK PENDIDIKAN STUDI KASUS DESA DI KECAMATAN PRAYA BARAT - Alimudin, Lalu; Azizah, Yupiatul; Mustari, Mohammad (CV. Lafadz Jaya, 2024)
This research aims to analyze the Village Head's decisions in allocating village funds for the education sector in the Praya Barat District. The allocation of village funds is a policy that can impact the development of various sectors, including education. This study uses a qualitative approach with a case study method, involving in-depth interviews with the Village Head, village officials, community leaders, and document analysis of the village budget. The data analysis technique used is qualitative descriptive analysis to identify patterns in the allocation of village funds. The results show that most of the village funds are allocated for improving educational facilities, such as renovating school buildings and providing educational tools. Additionally, village funds are used to give incentives to honorary teachers. However, the allocation of village funds in the education sector is still focused on physical development and lacks attention to improving teaching quality, such as teacher training and curriculum development. Factors influencing the Village Head's decision include village deliberations and applicable government policies. This study suggests that village fund allocation should be more balanced between physical development and quality education improvement, along with enhancing the capacity of village managers to plan and utilize village funds effectively.